Distribution of Water Phantom BNCT Cyclotron based Using PHITS - siti maimanah; siti maimanah; Susilo Susilo; Yohannes Sardjono (Indonesian Journal of Physics and Nuclear Applications, 2019)
This research purpose is to estimate the dose distribution of BNCT in water phantom. Some common methods in the treatment of cancer such as brakhiterapi, surgery, chemotherapy, and radiotherapy still have the risk of damaging healthy tissue around cancer cells. BNCT is a selectively-designed technique by targeting high-loaded LET particles to tumors at the cellular level. BNCT proves to be a powerful method of killing cancer without damaging normal tissue. The source of the neutron used from the cyclotron dose in water phantom with the size of 30 cm x 30 cm x 30 cm was calculated using PHITS program. The result from the simulation is that boron water panthom has a dosimetri higher than phantom water without boron.